Elevated neurotensin levels among obese adolescents may be related to emotion dysregulation and impulsivity: a cross-sectional, case-control study - Özyurt, Gonca; Cingöz, Gülten; Öztürk, Yusuf; Küme, Tuncay; Dündar, Bumin Nuri; Tufan, Ali Evren; Çatlı, Gönül (The Turkish Journal of Pediatrics, 2022)
Background. In this study, we aimed to evaluate the serum neurotensin (NT) levels and their relationships with self-reported anxiety, emotion regulation skills and impulsivity in healthy and obese adolescents. Methods. Adolescents who gained weight between 12- 17 years of age and who were above the 95th percentile (p) for body mass index (BMI) > 95p were compared with age- and gender-matched healthy adolescents with a BMI of 3-85 p. Anthropometric measurements were performed, and serum NT levels were analyzed with ELISA method in all participants. Barrat Impulsivity Scale-11 (BIS-11), Screen for Child Anxiety Related Disorders (SCARED) and Difficulties in Emotion Regulation Scale (DERS) were used for evaluating self-reported impulsivity, anxiety and emotion regulation. MANOVA with follow-up univariate ANOVAs (Bonferroni corrected) were used for group comparisons. P was set at 0.05 (two-tailed). Results. Sixty-five obese and 65 healthy adolescents were included in the study. In the obese group, NT levels were significantly elevated compared to the control group. Self-reported emotion-regulation difficulties, anxiety and impulsivity were significantly elevated among obese adolescents. Serum NT levels among the obese group were positively correlated with emotion dysregulation and impulsivity scores. Conclusions. In this study, we found emotional dysregulation, anxiety, impulsivity, and serum NT levels were significantly elevated among obese adolescents compared to controls. NT levels in the obese group correlated with impulsivity and emotion dysregulation. Further studies should evaluate the potential role of NT in the etiology of psychopathology among adolescents who are obese.
Keywords: adolescent; anxiety; emotion regulation; neurotensin; obesity